Using automated voice calls to improve adherence to iron supplements during pregnancy: A pilot study - Thies, William; Cutrell, Edward; Pai, Niranjan; Supe, Pradnya; Kore, Shailesh; Nandanwar, Y.S.; Hegde, Aparna; Cutrell, Ed; Thies, Bill (Proceedings of ICTD 2013, the 6th International Conference on Information and Communication Technologies and Development, 2013)
For years, researchers have explored the use of mobile phone reminders to improve adherence to medication. However, few studies have measured the direct medical benefit of those reminders, especially for low-literate populations in the developing world. This paper describes the use of automated voice calls to promote adherence to iron supplements among pregnant women in urban India. Unlike prior studies, we assess impact via a direct measurement of hemoglobin (Hb) levels in the blood. We enrolled 130 pregnant women from a low-income area of Mumbai, India and randomly assigned them to control and treatment groups. Both groups received a counseling session and a free supply of medication. The treatment group also received short audio messages, three times per week for a period of three months, encouraging them to take iron supplements. Results suggest that auto- mated calls positively impacted Hb levels. However, because we could only recover 79 women for follow-up, and the effect size was small, our results lack statistical power (aver- age change in Hb = 0.43 g/dL, 95% CI = -0.13 - 0.98 g/dL, p=0.13). We conclude that automated calls deserve further consideration for reducing maternal anemia, and we share our lessons learned for the benefit of future interventions.